THE EFFECT OF PEDAGOGIC COMPETENCE ON STUDENT LEARNING RESULTS AT SMPN 17 MAKASSAR - Nursyamsy Bte Alwi; Mansyur Mansyur; Nurul Haeriyah Ridwan (International Conference on Social and Islamic Studies, 2021)
This study aims to: 1) determine the pedagogical competence of teachers at SMPN 17 Makassar. 2) knowing the learning outcomes of students at SMPN 17 Makassar. 3) determine the effect of pedagogic competence on student learning outcomes of SMPN 17 Makassar. This study uses quantitative research with research methods in the form of ex-post facto research, and research instruments using questionnaires. The data used is primary data obtained by distributing online questionnaires to 36 respondents with purposive sampling technique, data processing is carried out with SPSS 20 with simple linear regression analysis techniques. The results of this study indicate that: 1) pedagogic competence at SMPN 17 Makassar is in the "good" category with an average score of 15 or 42% located in the interval 67-77. 2) student learning outcomes at SMPN 17 Makassar are in the "very good" category with an average score of 11 or 31% located in the interval 92-95. 3) significant test results with t-test obtained tcount 2.841 = 2.03, ttable when compared is 2.841 > 2.03, meaning that there is a significant influence between teacher pedagogic competence on student learning outcomes at SMPN 17 Makassar. The results showed that the teacher's pedagogic competence gave 52%. The implication of this research is that the principal of the training school makes training or seminars on teacher competence that must be followed by teachers in order to master and improve teacher competence, especially pedagogics so that they can help students have better learning outcomes.